Pendekatan Komunikasi Injil Lintas Budaya terhadap Tradisi Bong Pay Etnis Tionghoa - Lukmono, Irawan Budi; Stefani, Sarah (Sekolah Tinggi Teologi Kharisma, 2021)
The important task of Christians is to carry out the Great Commission. Every Christian must share his life with Christ to the world around him. The world around here includes ethnic groups in Indonesia. One of the ethnic groups who need the gospel of Christ in Indonesia is the Chinese who practice bong pay, so that their ancestors will bless their future descendants. The purpose of this study was to find a cross-cultural gospel communication strategy in the Chinese ethnic bong pay tradition. This study uses a qualitative approach with hermeneutic (exegesis) methods, interviews, and literature studies. The result of this research is a cross-cultural gospel communication approach to the Chinese ethnic bong pay tradition, based on Colossians 2: 6-15 which includes: communicator, communicant, news content, and means of communication (channel of communication). Tugas penting orang Kristen adalah melaksanakan Amanat Agung. Setiap orang Kristen harus bersaksi mengenai kehidupan mereka bersama Kristus kepada dunia sekitar. Dunia sekitar di sini termasuk suku atau etnis di Indonesia. Salah satu etnis yang memerlukan Injil Kristus di Indonesia adalah etnis Tionghoa yang mempraktikkan bong pay, agar para leluhur memberkati keturunan selanjutnya. Tujuan penelitian ini untuk menemukan pendekatan komunikasi Injil lintas budaya dalam tradisi bong pay etnis Tionghoa. Penelitian ini menggunakan pendekatan kualitatif dengan metode hermeneutika (eksegesa), wawancara, dan studi literatur. Hasil dari penelitian ini adalah pendekatan komunikasi Injil lintas budaya terhadap budaya bong pay etnis Tionghoa berdasarkan surat Kolose 2:6-15 yang meliputi: komunikator, komunikan, isi berita, dan sarana komunikasi (saluran komunikasi).